(untitled) (Global Journal of Human-Social Science, 2017)
Feedback can have different forms and functions depending on its objectives as well as its provider teacher feedback student feedback peer feedback written feedback oral feedback etc One of the most constructive forms of feedback may be peer feedback since it involves group learning Van Gennip Segers and Tillema 2010 According to Topping 1998 p 250 peer feedback is an agreement in which individuals consider the amount level value worth quality or success of the products or outcomes of learning of peers of similar status Cunningham 1992 argues that the interaction and communication that result fromthe production of feedback get more important in online instructional courses than in face to face courses because in his view nothing can bring about learning more than the dialogue among the community members Hewitt 2000 and Tuzi 2004 also emphasize the importance of peer feedback in online environments and point out that in such environments peer feedback can influence the students outcomes more than in face-to-face environments because of the ease of communication as well as the absence of affective factors Thus researchers believe that deep learning can take place in online settings in which students give and receive feedback from one another in a calm stress-free and individualized environment What do we know about feedback from previous research